2020
DOI: 10.1007/s11104-020-04738-3
|View full text |Cite
|
Sign up to set email alerts
|

Root water uptake under heterogeneous soil moisture conditions: an experimental study for unraveling compensatory root water uptake and hydraulic redistribution

Abstract: Aims Plant roots often encounter heterogeneity in soil water content and respond by compensating water uptake from wet zones to cope with the transpiration demand. Simultaneously, plants may also exhibit rootmediated hydraulic redistribution from wet to dry zones. Experiments were conducted to simultaneously monitor compensated root water uptake and hydraulic redistribution in the vadose zone. Methods Vertical and horizontal split-root lysimeters were used to hydraulically isolate maize roots under altering so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 99 publications
(132 reference statements)
0
9
1
1
Order By: Relevance
“…Although previous studies at the species level showed that soil moisture and rock fragment content played key roles in determining plants' water use patterns (Cai et al, 2018;Korboulewsky et al, 2020;Tetegan et al, 2015;Thomas et al, 2020), we found that deep water utilization parameters of the tree and shrub layers had weak associations with the substrate characteristics. With the exception of the DWP of the herb layer being associated with the soil water content in the 0-60 cm layer, there was no significant relationship between soil properties and DW (or DWP) of the tree and shrub layers (Tables S2 and S3).…”
Section: Differences In Deep Water Use Strategies Among and Within Li...contrasting
confidence: 89%
“…Although previous studies at the species level showed that soil moisture and rock fragment content played key roles in determining plants' water use patterns (Cai et al, 2018;Korboulewsky et al, 2020;Tetegan et al, 2015;Thomas et al, 2020), we found that deep water utilization parameters of the tree and shrub layers had weak associations with the substrate characteristics. With the exception of the DWP of the herb layer being associated with the soil water content in the 0-60 cm layer, there was no significant relationship between soil properties and DW (or DWP) of the tree and shrub layers (Tables S2 and S3).…”
Section: Differences In Deep Water Use Strategies Among and Within Li...contrasting
confidence: 89%
“…Short‐term responses, potentially enabling compensated uptake without changes in root distribution, are less understood. Possible drivers and explanations for short‐term changes in uptake patterns are simple hydrology based on the movement towards equilibrium of potential energy gradients, regulation of hydraulic conductivity within the roots as water moves from the root surface to the xylem via cell membranes, and root‐mediated hydraulic redistribution (Bazihizina et al., 2012; Cai et al., 2018; Lei et al., 2019; Steudle, 2000; Thomas et al., 2020). Differential changes in hydraulic conductivity in different parts of the root zone of a single plant may improve plant scale efficiency of water uptake by allowing more uptake from regions with higher water potential where water is more readily available.…”
Section: Introductionmentioning
confidence: 99%
“…Jackson et al (2000) vermelden dat er -destijds -voor minstens vijftig gewassoorten aangetoond is dat deze processen kunnen optreden, onder allerlei klimatologische omstandigheden. Maar er zijn ook studies die concluderen dat de herverdeling moeilijk meetbaar is, zoals in de lysimeterstudie waarin kunstmatig natte en droge zones werden opgelegd waaruit wel bleek dat compensatie van wateropname plaatsvindt, maar waarbij niet voldoende bewijs voor herverdeling kon worden aangetoond (Thomas et al, 2020).…”
Section: Tabelunclassified